Extended reality and sustainable tourism: restorying human–wildlife relationships for biocultural conservation. Issue 1 (2nd January 2023) - Branstrator, Julia R.; Cavaliere, Christina T.; Xiong, Lina; Knight, David
ABSTRACT : Through a critical pedagogical framework, global conservation initiatives are integrated to curate a transformational extended reality (XR) curriculum in nature-based tourism (NBT). This proposed design affects visitors' protected area experience and supports human–wildlife relationships through XR exposure (before), peak NBT experiences (during), and post-experience reflections (after). The authors' XR design entitled Knowing Wolves (KW) is inspired by Colorado's publicly approved Gray Wolf reintroduction legislation and reorients the visitor experiencescape as a conduit for wildlife agency after exposure to critical thinking engagement for biocultural conservation. The authors analyze four international initiatives featuring human–wildlife criteria including the United Nations Sustainable Development Goals, the Global Sustainable Tourism Criteria, the Convention on Biological Diversity post-2020 Global Biodiversity Framework, and the Convention on International Trade in Endangered Species. The XR curriculum challenges practices of colonial conservation, integrates environmental intersectionality and critical inquiry to support engagement with posthumanism philosophy and agency of oppressed groups.